The story of rare earth elements (REEs): Occurrences, global distribution, genesis, geology, mineralogy and global production - Dushyantha, Nimila; Batapola, Nadeera; Ilankoon, I.M.S.K.; Rohitha, Sudath; Premasiri, Ranjith; Abeysinghe, Bandara; Ratnayake, Nalin; Dissanayake, Kithsiri (Ore geology reviews, 2020)
[Display omitted] •REEs are critical to several modern technologies, especially for green energy.•China dominates the RE industry producing more than 90% of the current requirements.•Secondary RE resources are becoming promising resources to cater the future demand.•Growing ecological concerns in RE industry need to be addressed sustainably. Rare earth elements (REEs) including fifteen lanthanides, yttrium and scandium are found in more than 250 minerals, worldwide. REEs are used in various high-tech applications across various industries, such as electrical and electronics, automotive, renewable energy, medical and defence. Therefore, the demand for REEs in the global market is increasing day by day due to the surging demand from various sectors, such as emerging economies, green technology and R&D sectors. Rare earth (RE) deposits are classified on the basis of their genetic associations, mineralogy and form of occurrences. The Bayan Obo, Mountain Pass, Mount Weld and China’s ion adsorption clays are the major RE deposits/mines in the world to date and their genesis, chronology and mineralogy are discussed in this review. In addition, there are other RE deposits, which are currently being mined or in the feasibility or exploration stages. Most of the RE resources, production, processing and supply are concentrated in the Asia-Pacific region. In this regard, China holds the dominancy in the RE industry by producing more than 90% of the current rare earth requirements. Thus, REEs are used as a powerful tool by China in trade wars against other countries, especially against USA in 2019. However, overwhelming challenges in conventional RE explorations and mining make secondary RE resources, such as electric and electronic waste (e-waste) and mine tailings as promising resources in the future. Due to the supply risk of REEs and the monopoly of the REEs market, REEs recycling is currently considered as an effective method to alleviate market fluctuations. However, economical and sustainable processing techniques are yet to be established to exploit REEs via recycling. Moreover, there are growing ecological concerns along with social resistance towards the RE industry. To overcome these issues, the RE industry needs to be assessed to maintain long-term social sustainability by fostering the United Nations sustainable development goals (SDGs).